The Aku-Ahwa and Aku-Maga post-burial rites of the Jukun peoples of northern Nigeria - Lane, Michael G. M. (International Library of African Music, 1959)
The records of the Jukun peoples of Northern Nigeria are as vague as those of most Nigerian tribes with the exception, perhaps, of the Fulani and the Hausa. It is thought that in the mid-fifteenth century they occupied the whole of the north-eastern corner of Nigeria and according to Fulani records they had gained the whole of the north two centuries later. One hundred years of glorious rule ended when they were defeated by the Fulani. Now they are only some 25,000 strong and they have been pushed back to the little triangular area round the banks of the Benue, Katsina and Donga rivers. Anthropologists suspect that the Jukun originally came from the Sudan and the greatest authority on the tribe, C. K. Meek, has called his major work about them “A Sudanese Kingdom”. The Jukun religion is based on the divine right of kingship, their king being referred to as “Aku”, meaning “Souls of the Dead”, while Sir Wallis Budge quotes the names “Khu” or “Aaku” given to the ancient Egyptian beatified souls. Another fact in our search for proof of this ancestry is the importance that is laid on the sun. Although it cannot be said that, like the Pharaohs, the king is the only son of the sun god, it is certainly true to say that the Jukun “Aku” is indeed the son of one of the gods. The most important of the gods is still the sun god and thus . . .? However, whether proven or not, it is interesting that in spite of centuries of mingling with the semi-Bantu people of the Middle Belt the Jukun have retained many characteristics which justify anthropological suspicions.
Keywords: Jukun (African people); Ethnomusicology; Funeral music; Musical instruments; Ethnology; Funeral Custom; Nigeria; African Music; Funeral Rite; Funeral Ceremony